The Short Form-6 Dimension (SF-6D) Validity and Reliability in Hemodialysis Patients - Anisa Zulfa Fatihah; Tri Murti Andayani; Nanang Munif Yasin (Universitas Airlangga, 2021)
Background: Quality of life becomes an important parameter that is needed for assessing the clinical outcome of patients undergoing long-term therapy for chronic diseases, such as chronic kidney failure. Short Form-6 Dimension (SF-6D) is one of the generic instruments that can be used to assess health-related quality of life (HRQOL). The psychometric properties SF-6D test in hemodialysis patients in Indonesia has never been conducted. Objective: Aimed to evaluate the reliability and validity of SF-6D questionnaire in Indonesian version in patients with chronic kidney failure. Methods: This is an observational study with a cross-sectional design involving 117 patients who meet the inclusion and exclusion criteria in the hemodialysis unit in Dr. Sardjito Central General Hospital and UGM Academic Hospital Yogyakarta. Results: The SF-6D questionnaire has good internal consistency, as seen in Cronbach's alpha value of 0.771. In this study, the ceiling effect test showed 6.8% (< 15%). The measurement of convergent validity was carried out using Spearman rho to analyze the correlation of the questionnaires and see its correlation with other instruments (KDQOL-SF36). Based on the research, the correlation coefficient value of 0.768 (> 0.75) indicates very good result for a strong correlation. The SF-6D instrument was able to distinguish the quality of life with a significant value (p < 0.05) in age, occupation, and comorbid groups. Conclusion: SF-6D questionnaire is valid and reliable, so it can be used to measure the HRQOL of hemodialysis patients. The mean SF-6D utility score of hemodialysis patients is high (0.7975 ± 0.1488).